Conclusion and possible future direction - Sasamal T.N.; Singh A.K.; Mohan A. (My University, 2025)
The QCA paradigm encodes bit information by charge configuration within a cell instead of current switches of transistors in conventional CMOS circuits. This revolutionary approach provides an alternate way for transistor-less computation at the nanoscale. This research has provided designs and simulation results for new nanoelectronics computing architecture-based digital design on the Quantum-dot Cellular Automata (QCA) paradigm. © Springer Nature Singapore Pte Ltd 2020.